2019
DOI: 10.1109/access.2019.2955715
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Measured and Computed Assessments of the RF Exposure Compliance Boundary of an In-Situ Radio Base Station Massive MIMO Antenna

Abstract: Advanced antenna technology in the form of massive multiple input multiple output (mMIMO) antennas has been deployed in fourth generation (4G) long term evolution (LTE) mobile networks and will be a standard feature in fifth generation (5G) networks. A characteristic of mMIMO is beamforming in which a large array of antenna elements is used to concentrate energy in specific narrow directions to improve data throughput. Assessing the electromagnetic field (EMF) compliance boundary around a beamforming capable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 5 publications
3
15
0
Order By: Relevance
“…According to a technical report from the International Electrotechnical Commission [15], the actual maximum transmit power predicted for a massive MIMO site with horizontal beam scanning would only correspond to about 25% (−6 dB) of the theoretical maximum (including the effect of 75% TDD downlink duty cycle). Such values are consistent with measurements previously conducted on massive MIMO BSs of commercial 4G networks [10,11]. In [10], the actual maximum exposure was found to be about 8.5 dB lower than the theoretical maximum by using network counters like those utilized in this paper.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…According to a technical report from the International Electrotechnical Commission [15], the actual maximum transmit power predicted for a massive MIMO site with horizontal beam scanning would only correspond to about 25% (−6 dB) of the theoretical maximum (including the effect of 75% TDD downlink duty cycle). Such values are consistent with measurements previously conducted on massive MIMO BSs of commercial 4G networks [10,11]. In [10], the actual maximum exposure was found to be about 8.5 dB lower than the theoretical maximum by using network counters like those utilized in this paper.…”
Section: Discussionsupporting
confidence: 90%
“…According to [8], the 95th percentile of the transmitted power per beam would range between 7% and 22% of the theoretical maximum. These results have been verified by measurements conducted on massive MIMO BSs [10,11] of 4G LTE-Advanced networks. While a substantial amount of research available to date already shows that massive MIMO BSs do not constantly operate at the maximum power, experimental data specific for 5G live networks are yet not available.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…From an environmental point of view, several recent surveys, reviews and meta-analysis studies can be found in the literature, where RF-EMF exposure levels are discussed [6-11, 18, 57-62], usually performing dynamic campaigns of measurements with RF-EMF frequency-selective exposimeters (PEM) and volunteers' help. As in the previous research works, similar conclusions have been obtained: generally, RF-EMF exposure levels over a broad frequency range are very low in a general life context (with exposure levels well below 1 V/m) when compared with current established international RF-EMF exposure limits [33,48,[63][64][65] presenting higher mean exposure levels for public transportation systems environments (considered complex heterogeneous environments in terms of radio wave propagation) [59][60][66][67]. In this sense, worst exposure average levels are obtained for rail transportation wagon cars scenarios, where the metal structure influence, the supplying electric lines and towers and particularly their huge passenger affluence (high density cellular use environments), involves much more challenging propagation phenomena [60,[68][69][70].…”
Section: B Environmental Exposuresupporting
confidence: 86%
“…In many cases, the motivation to carry out the research was to find cellular evidence to back up the claimed efficacy of therapy devices, rather than the safety of telecommunication systems. Measurements of massive MIMO systems (as an indication of possible exposures following 5G roll-out) indicate that PDs at the occupational compliance boundary are below 16.1% of the occupational limits (which were 50 W/m 2 at the time of that study) [ 13 ]. Using a value of 0.005 W/kg/W/m 2 at these frequencies [ 10 ] implies a whole-body average of 50 × 0.161 × 0.005 = 0.04 W/kg at maximum (for the general public, the maximum values are at least 10× less).…”
Section: Discussionmentioning
confidence: 99%